The Thermodynamic Driving Force During Double Recalescence in Iron Cobalt. - Chouinard, Veronica. (Tufts Archival Research Center, 2019)
Abstract: The rapid solidification behavior of Fe-Co was examined using electromagnetic and electrostatic levitation. As predicted by equilibrium phase diagram, double recalescence was observed. The delay time between the nucleation of the primary metastable bcc ferrite phase and the secondary stable fcc austenite phase was successfully measured using a high-speed camera. Results have shown that delay times are significantly different between the highly convective environment of the electrostatic levitator and the quiescent conditions of the electrostatic levitator. Alloys with different thermodynamic driving forces were selected and compared for this investigation. It was found that alloys with different thermodynamic driving forces have different delay times. Shorter delay times were confirmed to be the result of higher thermodynamic driving forces. For a given alloy, the degree of undercooling has been shown to significantly affect delay time between primary and secondary recalescence. However, in contrast to the plate morphology seen in ternary steel alloys, Kantrowitz's model for nucleation indicates a preference for spherical geometry in Fe-Co alloys.